Processo de trabalho e gestão do cuidado nos serviços de atenção secundária em saúde bucal no Brasil - Cruz, Danilson Ferreira da (2024)
The Unified Health System (SUS) aims to provide more democratic access to health actions and services, guided by the principles of integrality, universality and equity. In the field of oral health, the SUS has brought to Brazilian dentistry the challenge of reformulating its practices so that these principles are guaranteed. In 2004, the National Oral Health Policy was launched, the initial milestone in an extensive process of debate and the construction of strategies that proposed a reorientation of the techno-assistance model in various components, with the structuring of secondary care, based on the creation of Dental Specialty Centers, being a structuring component of this policy. A decade after the implementation of these services, the Ministry of Health created the Program for Improving Access and Quality of Dental Specialty Centers (PMAQ-CEO), which aimed to monitor oral health services and ensure greater access and quality of these services to the population. In this context, the aim of this study was to evaluate the management of the Dental Specialty Centers according to the data related to the organization of the teams' work process set out in Module II of the final report on the results of the 2nd Cycle of the National Program for Improving Access and Quality (PMAQ-CEO II). To this end, a quantitative, evaluative and cross-sectional study was carried out. The data used in this investigation was extracted from Module II of the PMAQ/CEO external evaluation interviews, which is the result of the application of an instrument to verify the standards of access and quality achieved by the professionals and management of the CEOs. We used data from interviews with professionals and managers from 1042 CEOs in Brazil in 2018. Two evaluation indices were developed: the CEO Strategic Management Evaluation Index (IAGE- CEO) and the CEO Operational Management Evaluation Index (IAGO-CEO). For the first, questions related to the strategic management of CEOs were identified, such as planning, monitoring, evaluation, matrix support and continuing health education. For the second index, questions related to the operational management of services were selected, such as the organization of medical records, characterization of demand, and organization of the agenda and protocols agreed between the CEO and the healthcare network. The data was tabulated and analyzed using the Statistical Package for Social Sciences software (IBM SPSS, v.24, IBM), with a significance level of 5%. The data was initially analyzed descriptively. Bivariate correlations were analyzed using Spearman's correlation test. Variables with a correlation coefficient below 0.3 in relation to the IAGE-CEO were excluded from the analysis. Cronbach's alpha coefficient, the Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy and the significance of Bartlett's test were calculated. The exploratory factor analysis defined which variables made up the main components of the IAGE-CEO. For the IAGO-CEO, exploratory factor analysis was used and required the analysis of 24 questions from the PMAQ-CEO external evaluation questionnaire (2nd evaluation cycle). Of these, 16 variables were included in the final model, which resulted in 4 factors, namely: Waiting List Management, Absenteeism, Electronic Health Record and Clinical Protocols. The results are systematized separately by index. Principal component analysis showed that 49.95% of the variance in the IAGE-CEO is explained by two main components: a) team planning and continuing health education and b) management, evaluation and matrix support for the CEO. The regression analysis showed that the IAGO-CEO index was responsible for explaining 20.3% of the variance in the certification score for the 2nd cycle of external evaluation of the PMAQ-CEO. Only the waiting list management component showed no statistical association with the CEO certification score. Finally, based on the validation of the indices, this study, with a view to building a Decision Model, developed an application called APP G-CEO, which includes the set of questions validated in the indices. This application is easy to use and low-cost so that managers can develop evaluation and monitoring processes for CEO management actions. The conclusion is that the formulation and validation of evaluation indices for DSCs helped to identify aspects that qualify the work process of service management beyond the physical structure of these services and that the systematization of these evaluation indices in the G-CEO APP tool is a possibility for managers to use to evaluate DSCs and qualify their decision-making processes with the results generated.